An improved PSO algorithm for smooth path planning of mobile robots using continuous high-degree Bezier curve - Song, Baoye; Wang, Zidong; Zou, Lei (Applied soft computing, 2021)
In this paper, a new strategy is developed to plan the smooth path for mobile robots through an improved PSO algorithm in combination with the continuous high-degree Bezier curve. Rather than connecting several low-degree Bezier curve segments, the use of continuous high-degree Bezier curves facilitates the fulfillment of the requirement of high-order continuity such as the continuous curvature derivative, which is critical for the motion control of the mobile robots. On the other hand, the smooth path planning of mobile robots is mathematically an optimization problem that can be dealt with by evolutionary computation algorithms. In this regard, an improved particle swarm optimization (PSO) algorithm is proposed to tackle the local trapping and premature convergence issues. In the improved PSO algorithm, an adaptive fractional-order velocity is introduced to enforce some disturbances on the particle swarm according to its evolutionary state, thereby enhancing its capability of jumping out of the local minima and exploring the searching space more thoroughly. The superiority of the improved PSO algorithm is verified by comparing with several standard and modified PSO algorithms on some benchmark functions, and the advantages of the new strategy is also confirmed by several comprehensive simulation experiments for the smooth path planning of mobile robots. •In this paper, a new strategy is developed to plan the smooth path for mobile robots.•An improved PSO algorithm is proposed in combination with the continuous high-degree Bezier curve.•An adaptive fractional-order velocity is introduced to enforce some disturbances on the particle.•The superiority of the improved PSO algorithm is verified by comparing with several standard benchmark functions.•The advantages of the new strategy is also confirmed by simulation experiments for the smooth path planning of mobile robots.